A COMPREHENSIVE REVIEW OF NEUROBIOLOGICAL MECHANISMS DRIVING THE EFFECTS OF YOGA ON MENTAL HEALTH - Singh, Virendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Yoga has been found to promote positive changes in brain function strengthening areas that help regulate emotions and decision-making while also improving the balance of chemicals that contribute to mood stability. The practice encourages relaxation and helps the body shift into a calmer state reducing stress and anxiety through mindful breathing and exercises. Additionally, yoga supports the body's natural ability to manage stress by lowering excessive levels of stress hormones and fostering a more balanced physiological response. It also plays a key role in sharpening mental focus and breaking cycles of negative thought patterns helping individuals develop greater clarity and emotional resilience. The benefits of yoga extend to various mental health conditions that include anxiety, depression, and trauma-related disorders providing an accessible and holistic approach to psychological well-being. Furthermore, yoga's influence on brain health contributes to long-term emotional stability, supporting mental clarity and helping maintain cognitive sharpness over time. This study explores the growing understanding of how yoga influences mental health and the underlying mechanisms that explain how yoga enhances emotional well-being, cognitive function, and is effective in overall stress management. The interconnected effects of yoga on multiple neurobiological systems suggest its utility in preventive mental health care, facilitating emotional stability, stress adaptability, and optimized cognitive performance.